THREATS TO THE ECONOMIC SECURITY OF THE STATE: THE NATURE, STRUCTURE AND WAYS OF OVERCOMING - Holynska , O.; Odnostalko, D. (Pressing Problems of Public Administration, 2020)
The article reveals the essence and structure of the concept of “threat to the economic security of the state”. In theory, the problem of identifying threats to economic security depends directly on how the subject of security is determined and the vital interests of the individual, society and state are identified. Therefore, threats to economic security as a scientific category cannot exist in isolation. Only after identifying what is hazardous to life in general and economic, in particular, can the sources of risks, challenges and threats be identified. Therefore, “danger” is an initial concept for identifying risks.Scientific and theoretical approaches to the classification of threats to the economic security of the state are generalized. It is established that the most common is their division by place of origin into internal and external with respect to the security object. External threats occur in the external environment of the object, and internal threats are caused by the state of the security object itself.The main risk factors and threats that negatively affect the economic and financial situation in Ukraine are investigated. The main “poles” of threats to the economic security of modern Ukraine are the attraction of an economically attractive EU labor market and the pressure of an aggressive but wealthier Russian Federation.The ways of overcoming the threats to the economic security of the state are identified, among which are: intensification of scientific researches in the sphere of struggle in the economic sphere; a clear fixation of threats in top-level government documents with appropriate measures to counteract them will help to understand the current difficult situation; creating open and transparent conditions for human development; eliminating opportunities for corruption and arbitrary application of legislation; improving the level of protection of property rights through the improvement of the justice system; liquidation of the socio-economic base of organized crime in the sphere of economy and its merging with state authorities (including law enforcement) and local self-government bodies.